2002
DOI: 10.1073/pnas.062605899
|View full text |Cite
|
Sign up to set email alerts
|

Profound defects in pancreatic β-cell function in mice with combined heterozygous mutations in Pdx-1 , Hnf-1 α, and Hnf-3 β

Abstract: Defects in pancreatic ␤-cell function contribute to the development of type 2 diabetes, a polygenic disease that is characterized by insulin resistance and compromised insulin secretion. Hepatocyte nuclear factors (HNFs) -1␣, -3␤, -4␣, and Pdx-1 contribute in the complex transcriptional circuits within the pancreas that are involved in ␤-cell development and function. In mice, a heterozygous mutation in Pdx-1 alone, but not Hnf-1␣ ؉/؊ , Hnf-3␤ ؉/؊ , or Hnf-4␣ ؉/؊ , causes impaired glucose-stimulated insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 29 publications
(30 reference statements)
6
73
1
Order By: Relevance
“…Expression of Pdx-1-regulating Transcription Factor Genes in Irs2 Ϫ/Ϫ Murine ␤-Cells-HNF3␤ and HNF1␣ reportedly regulate the expression of Pdx-1 in vivo and in vitro (33). Contrary to a previous report (37), real time quantitative PCR study revealed Hnf3␤ and Hnf1␣ mRNA expressions to not be decreased when ␤-actin was selected as an internal control (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Expression of Pdx-1-regulating Transcription Factor Genes in Irs2 Ϫ/Ϫ Murine ␤-Cells-HNF3␤ and HNF1␣ reportedly regulate the expression of Pdx-1 in vivo and in vitro (33). Contrary to a previous report (37), real time quantitative PCR study revealed Hnf3␤ and Hnf1␣ mRNA expressions to not be decreased when ␤-actin was selected as an internal control (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Ϫ/Ϫ Murine ␤-Cells-Pdx-1 regulates the expressions of various pancreatic genes, including insulin, glucose transporter type 2 (Glut2) (29,41,42), and Nkx6.1 (32,33). The immunohistochemical results with anti-insulin, anti-Glut2, and anti-Nkx6.1 antibodies showed expression of these three proteins to be well preserved in Irs2 Ϫ/Ϫ murine islets, consistent with our previous observation that both glucose-induced insulin secretion and insulin contents were preserved (11) (Figs.…”
Section: Expression Of Pdx-1-regulated Downstream Genes In Irs2mentioning
confidence: 99%
“…Since Kushner et al reported that transgenic overexpression of Pdx1 restored beta cell mass in Irs2 −/− mice [28], Pdx1 may play a role in regulating beta cell mass. Nevertheless, because a haploinsufficiency of Pdx1 led to impaired beta cell function, but not to decreased beta cell mass [30], and because beta cell mass was smaller in our Irs2 −/− mice than in wild-type mice despite the Pdx1 expression level being maintained [29], two different pathways are involved in the stimulation of beta cell function and proliferation by a GKA.…”
Section: P22 Phox Expression (Au)mentioning
confidence: 99%
“…The expression of GLUT-2 has been shown to be up-regulated by glucose in pancreatic ␤ cells (4 -6). The regulation of glucokinase gene expression by glucose remains unclear (7,8); however, several of the transcription factors required for its expression are also involved in glucose regulation of gene expression (9).…”
mentioning
confidence: 99%